Nonmanuals in sign language - Herrmann, Annika; Steinbach, Markus (Benjamins current topics ;, 2013)
Computer-generated three-dimensional animation holds great promise for synthesizing utterances in American Sign Language (ASL) that are not only grammatical, but well-tolerated by members of the Deaf community. Unfortunately, animation poses several challenges stemming from the necessity of grappling with massive amounts of data. However, the linguistics of ASL may aid in surmounting the challenge by providing structure and rules for organizing animation data. An exploration of the linguistic and extralinguistic behavior of the brows from an animator's viewpoint yields a new approach for synth.